2017
DOI: 10.1371/journal.pone.0174252
|View full text |Cite
|
Sign up to set email alerts
|

High school science fair and research integrity

Abstract: Research misconduct has become an important matter of concern in the scientific community. The extent to which such behavior occurs early in science education has received little attention. In the current study, using the web-based data collection program REDCap, we obtained responses to an anonymous and voluntary survey about science fair from 65 high school students who recently competed in the Dallas Regional Science and Engineering Fair and from 237 STEM-track, post-high school students (undergraduates, 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 13 publications
5
30
0
1
Order By: Relevance
“…The goal of our ongoing research is to identify strengths and weaknesses of high school level science fair and improvements that can help science educators make science fair a more effective, inclusive and equitable learning experience. Previously, we reported findings regarding students' high school science fair experiences based on a regional group of high school students who had competed in the Dallas Regional Science and Engineering Fair (DRSEF) and post high school students on STEM education tracks doing research at UT Southwestern Medical Center [10,11]. In the current paper, we confirm and extend the previous findings.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The goal of our ongoing research is to identify strengths and weaknesses of high school level science fair and improvements that can help science educators make science fair a more effective, inclusive and equitable learning experience. Previously, we reported findings regarding students' high school science fair experiences based on a regional group of high school students who had competed in the Dallas Regional Science and Engineering Fair (DRSEF) and post high school students on STEM education tracks doing research at UT Southwestern Medical Center [10,11]. In the current paper, we confirm and extend the previous findings.…”
Section: Discussionsupporting
confidence: 87%
“…A potential limitation of our study is the small size of the study population relative to the total number of students participating. Nevertheless, we observed many overlapping features of science fair experience between the low response rate/large data set (Scienteer national) compared to the high response rate/small data set (DRSEF regional) described previously [10,11]. Articles on the internet, teachers, and parents were the main sources of help; time pressure and coming up with the idea were the main obstacles; more background research and perseverance were the main ways to overcome obstacles; fine-tuning the report and developing the idea were important types of help Page 11 received.…”
Section: Discussionsupporting
confidence: 54%
“…Esse autor considera que é preciso desenvolver políticas que visem reduzir o plágio, de acordo com quatro princípios. Entre eles estariam os que ele chamou de pedagógicos, o que incluiria atividades de orientação aos estudantes, por meio do desenvolvimento de materiais e recursos específi cos. A importância de trazermos já para o nível do ensino médio a discussão sobre a condução adequada de uma pesquisa é destacada por Dias (2017) e Grinnell et al (2017). Essa ação estimularia o aluno a conhecer o processo de construção de um texto científi co, incluindo informações sobre paráfrase e referenciamento, no âmbito de uma produção autoral.…”
Section: Figuraunclassified
“…Another informal approach to science education is participation in science fairs, which provide students the opportunity to explore and showcase their knowledge about a specific science concept. As an informal science venue, science fair projects do not need to align with state educational standards, allowing students to explore STEM interests outside the scope of the classroom (Schmidt and Kelter, 2017;Grinnell et al, 2017). Science fairs emphasize individual student participation and, as a mechanism to promote parental engagement, this structure may have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…When surveyed, Grinnell et al (2017) found that 47% of high school students indicated receiving assistance with science fair projects from parents. However, given science fairs are intended to showcase individual student achievement, the question remains as to an acceptable level of parental engagement.…”
Section: Introductionmentioning
confidence: 99%